Governments, entrepreneurs, and positive externalities: A real options perspective - Lee, S.; Peng, Mike; Song, S. (Elsevier, 2013)
This article extends the real options view from the firm level to the societal level, by exploring how government policies facilitate entrepreneurship development. Governments can focus on generating positive externalities, as opposed to avoiding failure for individual firms. Treating the bundle of productive assets within a country as entrepreneurial options, government policies concentrated on maximizing the variance of such a bundle would facilitate entrepreneurship development. Propositions are generated for six policy domains: (1) tax policies, (2) industry structure and entry barriers, (3) foreign direct investment, (4) opening foreign markets, (5) bankruptcy legislations, and (6) moving away from traditional industrial protection.